2022
DOI: 10.3389/fimmu.2022.985472
|View full text |Cite|
|
Sign up to set email alerts
|

Assessment of plasma Catestatin in COVID-19 reveals a hitherto unknown inflammatory activity with impact on morbidity-mortality

Abstract: IntroductionNeuroendocrine cells release Catestatin (CST) from Chromogranin A (CgA) to regulate stress responses. As regards COVID-19 patients (COVID+) requiring oxygen supply, to date nobody has studied CST as a potential mediator in the regulation of immunity.Patients & MethodsAdmission plasma CST and CgA - its precursor - concentrations were measured (ELISA test) in 73 COVID+ and 27 controls. Relationships with demographics, comorbidities, disease severity and outcomes were analysed (Mann-Whitney, S… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 49 publications
0
3
0
Order By: Relevance
“…Importantly, admission values of CGA significantly increased in those multiple trauma patients who subsequently developed a nosocomial infection: a concentration of 67 ng/mL predicted this occurrence with a sensitivity of 100% and a specificity of 70%, leading to a negative likelihood ratio of almost zero. Recently, we confirmed that admission CGA achieved similar performance for predicting nosocomial infections in COVID patients requiring oxygenation support [ 14 ]. This suggests that CGA may reflect not only the triggering disease but also the neuro-hormonal response by the neuroendocrine tissues.…”
Section: Cga and Vasostatin-i (Cga1-76) Are Biomarkers Of Severity In...mentioning
confidence: 52%
See 1 more Smart Citation
“…Importantly, admission values of CGA significantly increased in those multiple trauma patients who subsequently developed a nosocomial infection: a concentration of 67 ng/mL predicted this occurrence with a sensitivity of 100% and a specificity of 70%, leading to a negative likelihood ratio of almost zero. Recently, we confirmed that admission CGA achieved similar performance for predicting nosocomial infections in COVID patients requiring oxygenation support [ 14 ]. This suggests that CGA may reflect not only the triggering disease but also the neuro-hormonal response by the neuroendocrine tissues.…”
Section: Cga and Vasostatin-i (Cga1-76) Are Biomarkers Of Severity In...mentioning
confidence: 52%
“…They showed that dying COVID patients demonstrated higher CGA levels on admission than survivors. Indeed, in our differently designed study of COVID patients admitted for acute respiratory failure and hypoxemia, admission plasma CGA concentrations instead predicted the occurrence of morbidity rather than mortality, which was better forecast by the CAT/CGA ratio [ 14 ]. Our study suggested that the stressing challenge of COVID was probably not hypoxemia itself—in line with its effect in vitro—since matched ICU control patients without hypoxemia did display levels of CGA similar to those of hypoxic COVID patients [ 37 ].…”
Section: Enigma and Future For Cga And Its Derived Peptides In The Cr...mentioning
confidence: 99%
“…Another important application for MF-AMPs in human health is their roles as the biomarkers of several diseases both related and unrelated to infections [28][29][30][31]. In this Special Issue, Scnheider and collaborators summarized the biomarker profile of CgA and its derived antimicrobial peptides in the context of critically ill patients [4].…”
mentioning
confidence: 99%